Translanguaging in The Indah G Show: Adultery, Infidelity and Homewrecking FT. Davina Karamoy of 'Ipar Adalah Maut' (PANOPTICON: Journal of English Studies, 2025)
This study aims to analyse the types and function of translanguaging used in the conversation between Indah and Davina on the Indah's G show YouTube channel. In this study, the writer uses descriptive qualitative method to explain the data by following Garcia & Otheguy (2014) and Garcia & Otheguy (2015) the theory of translanguaging to answer the statement of problems. This study indentifies 21 the types of translanguaging: 6 basic words insertion, 1 invented words insertion, 6 loan words insertion, 6 phrase words insertion, 1 reduplication words insertionan, and 1 regional particle insertion. In addition, 2 influenced by cognitive function, 11 influenced by communicative function, 8 influenced by social or expressive functions. The data finding found that Indah is the dominant use the types of translanguaging during the conversation. As a result, Indah used translanguaging to be more communicative while discussing some of significant topics with Davina in the conversation.